Halal-Thayyib, Food Products, and the Halal Industry: A Thematic Analysis on the Verses of the Qur'an - Wawan Arwani; Aan Jaelani; Slamet Firdaus; Tica Fatichah Hanim (UIN Siber Syekh Nurjati Cirebon, 2022)
This article aims to analyze the literary sources of the term halal-thayyib and its use in the Qur'an which has implications for the process of food products that are experiencing rapid development in the global halal industry. Thematic analysis is used as an approach in understanding and analyzing a text on the term halal-thayyib which is mentioned in several verses of the Qur'an. The use of terms and their forms will be collected, classified, validated, and interpreted in accordance with the applicable rules in the study of Arabic texts and the study of commentary. The text will be interpreted and analyzed to gain an understanding of halal food products. The results of the research confirm that the term halal -thayyib is used differently in context and space-time of meaning, even though its use is the same to explain legal provisions regarding food. The scientific cues in the verses of the Qur'an have implications for the types and sources of food, production processes, and product innovations that require halal criteria for consumption from a health perspective, healthy and clean food features, legal criteria for halal food products, and are developed to create a halal product guarantee system. These criteria are requirements for halal certification for food products that require a halal ecosystem in order to have market competitiveness in the development of the global halal industry.